2020
DOI: 10.1146/annurev-biochem-011520-105053
|View full text |Cite
|
Sign up to set email alerts
|

Mucins and the Microbiome

Abstract: Generating the barriers that protect our inner surfaces from bacteria and other challenges requires large glycoproteins called mucins. These come in two types, gel-forming and transmembrane, all characterized by large, highly O-glycosylated mucin domains that are diversely decorated by Golgi glycosyltransferases to become extended rodlike structures. The general functions of mucins on internal epithelial surfaces are to wash away microorganisms and, even more importantly, to build protective barriers. The latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
257
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(260 citation statements)
references
References 143 publications
1
257
0
2
Order By: Relevance
“…The amino acid Pro, instead, ensures that the structure of the mucins remains unfolded in the Golgi apparatus, allowing the O-glycosylation process (all the chemical steps are detailed in figures 1 and 2 ). 1 5 More than 80% of the mucin mass is made up of O-glycans and O-glycosylation is the main modification and type of glycosylation that affects mucins. 1 6 7 O-glycosylation represents an important process allowing the creation of a glycan coat, hiding the protein core of the mucins and protecting it from endogenous protease degradation, in addition to conferring the capacity to bind and be soluble in water and to form a gel.…”
Section: Mucus Structure and Organisationmentioning
confidence: 99%
See 2 more Smart Citations
“…The amino acid Pro, instead, ensures that the structure of the mucins remains unfolded in the Golgi apparatus, allowing the O-glycosylation process (all the chemical steps are detailed in figures 1 and 2 ). 1 5 More than 80% of the mucin mass is made up of O-glycans and O-glycosylation is the main modification and type of glycosylation that affects mucins. 1 6 7 O-glycosylation represents an important process allowing the creation of a glycan coat, hiding the protein core of the mucins and protecting it from endogenous protease degradation, in addition to conferring the capacity to bind and be soluble in water and to form a gel.…”
Section: Mucus Structure and Organisationmentioning
confidence: 99%
“… 1 5 More than 80% of the mucin mass is made up of O-glycans and O-glycosylation is the main modification and type of glycosylation that affects mucins. 1 6 7 O-glycosylation represents an important process allowing the creation of a glycan coat, hiding the protein core of the mucins and protecting it from endogenous protease degradation, in addition to conferring the capacity to bind and be soluble in water and to form a gel. 1 7 8 Glycosylation differs along the different regions of the digestive tract and among individuals, depending on the expression of glycosyltransferases, the state of health or disease and microbial colonisation.…”
Section: Mucus Structure and Organisationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a physical barrier, it separates external substances, enzymes, and bacteria from the epithelium. It was recently suggested that intestinal mucus forms three lines of defense against bacteria [22]. Firstly, through the physical inner mucus layer barrier, secondly, via the sentinel goblet cell response, and thirdly, through the crypt goblet cellemptying response.…”
Section: Mucus Layer Functionmentioning
confidence: 99%
“…Mucin domains are modular protein domains that adopt rigid and extended bottle-brush like structures due to a high density of O-glycosylated serine and threonine residues [1][2][3] . Mucin-type O-glycans are characterized by an initiating α-N-acetylgalactosamine (α-GalNAc) monosaccharide that can be further elaborated into several core structures through complex regulation of glycosyltransferases 4,5 .…”
Section: Introductionmentioning
confidence: 99%